1991
DOI: 10.1128/jb.173.8.2420-2424.1991
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Escherichia coli to cloacin DF13 involves the major outer membrane protein OmpF

Abstract: Fourteen spontaneous cloacin DF13-insensitive mutants of an Escherichia coli strain expressing the aerobactin-cloacin DF13 receptor protein IutA were isolated. The mutants fell into three classes on the basis of outer membrane profiles analyzed by electrophoresis in denaturing polyacrylamide gels. The most frequent class lacked the lutA protein and was unable to bind cloacin DF13 or aerobactin. A second class of mutants had lost protein species corresponding in size to the porin proteins OmpF and OmpC. To dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…This strain was completely resistant to lysis by either bacteriophage K20 or colicin N, whereas the isogenic ompF+ strain MC4100 was susceptible to both. Therefore, our results do not support the conclusions by Wooldridge and Williams (36) and demonstrate that OmpF is not involved directly in cloacin DF13 susceptibility. Nevertheless, it is possible that OmpF may play a minor role in the cloacin susceptibility of E. coli because we observed that MH610 was slightly less sensitive to cloacin (two serial dilutions) than the parent strain MC4100 (Fig.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…This strain was completely resistant to lysis by either bacteriophage K20 or colicin N, whereas the isogenic ompF+ strain MC4100 was susceptible to both. Therefore, our results do not support the conclusions by Wooldridge and Williams (36) and demonstrate that OmpF is not involved directly in cloacin DF13 susceptibility. Nevertheless, it is possible that OmpF may play a minor role in the cloacin susceptibility of E. coli because we observed that MH610 was slightly less sensitive to cloacin (two serial dilutions) than the parent strain MC4100 (Fig.…”
contrasting
confidence: 57%
“…Wooldridge and Williams recently reported that the major outer membrane protein OmpF was essential for the lethal action of cloacin DF13 in E. coli (36). It has been shown previously that toL4 and toiC mutations reduce the expression of OmpF (13,20).…”
mentioning
confidence: 99%
“…Changes in expression of the surface structures could also have an impact on the ability of UPEC to survive in a mouse or a human urinary tract. In addition, OmpR appears to regulate expression of enterochelin and the aerobactin receptor protein IutA (Oshima et al, 2002;Wooldridge & Williams, 1991). Iron acquisition is critical for UPEC survival in the urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…HM545299) was selected from preserved B. avium. (19) The aforementioned strain has a higher virulence and better cross-reactivity with other isolates of B. avium. The strains were cultured in bouillon medium at 37°C for 18 h. The bacteria were collected by centrifugation at 10,000 g for 15 min at 4°C, and then washed three times with chilled phosphatebuffered saline (PBS).…”
Section: Extraction and Purification Of Ompsmentioning
confidence: 99%